A project-based learning model in interpreting course - Andayani, Rika; Hanip Pujiati; Ibnu Agil (Lililacs Journal, 2023)
This research aims to design a project-based learning model to be utilized in interpreting courses. It employs the research and development methods with the Dick and Carey model. The stages of the research comprised instructional analysis, establishing assessment instruments, determining learning strategy, and constructing the learning materials. The research results revealed that the established project-based learning model was confirmed well-founded for teaching online interpreting courses regarding appraisals from the English language teaching assessment experts, materials experts, and future users. Accordingly, the established project-based learning model can be exploited to flourish the advancement of future lecturers to teach interpreting courses in an online environment